2022
DOI: 10.1029/2022ms002984
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Local Parameterization of Atmospheric Subgrid Processes With Neural Networks

Abstract: Accurate climate projections are of great societal relevance (e.g., in assessing the risk from heavy rainfall events) and scientific interest (e.g., in understanding the dynamics of the climate system). These projections rely on global climate models that typically have grid spacing of a few tens to a hundred kilometers and thus, cannot resolve processes that occur on smaller scales (i.e., subgrid processes). Because subgrid processes, such as convection and clouds, have important consequences for Earth's clim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…In a related study, Wang et al. (2022) show that including non‐local inputs improves offline performance for the NN momentum parameterization developed here, and future work should investigate its online performance. Overall, our results show that using high‐resolution simulations to evaluate subgrid fluxes provides useful information for the design of parameterizations, and that NN parameterization for momentum is a promising alternative to existing parameterizations.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In a related study, Wang et al. (2022) show that including non‐local inputs improves offline performance for the NN momentum parameterization developed here, and future work should investigate its online performance. Overall, our results show that using high‐resolution simulations to evaluate subgrid fluxes provides useful information for the design of parameterizations, and that NN parameterization for momentum is a promising alternative to existing parameterizations.…”
Section: Discussionmentioning
confidence: 77%
“…The staggering of momentum variables on the model grid poses challenging for learning a momentum parameterization and future work could investigate how best to deal with this issue which may improve online performance at all resolutions. In a related study, Wang et al (2022) show that including non-local inputs improves offline performance for the NN momentum parameterization developed here, and future work should investigate its online performance. Overall, our results show that using high-resolution simulations to evaluate subgrid fluxes provides useful information for the design of parameterizations, and that NN parameterization for momentum is a promising alternative to existing parameterizations.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, further tests, both offline and online (coupled), are needed to see if 3D GWP schemes improve the circulation variability in GCMs. That said, there is existing evidence for SGS modeling of other physical processes that would benefit from including neighboring columns, providing further incentive for considering horizontally non‐local parameterizations (e.g., Fatkullin & Vanden‐Eijnden, 2004; Guan et al., 2022; Wang et al., 2022). Adding to the complexity, we have found that the GWD due to SGS lateral momentum fluxes could be sensitive to the methods used to extract them.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The GCM’s column structure reflects the importance of separating the vertical in the model topology, and the importance of convection and its timescales in atmosphere and ocean. The structural independence of columns has been seen as a limitation, but new methods can use nonlocal predictors ( 102 ). The stochastic parameterizations mentioned in Section 3 also impose nonlocal (in space and time) coherence to the stochasticity ( 103 ).…”
Section: What Might a Future Modeling Landscape Look Like?mentioning
confidence: 99%